2021
DOI: 10.25124/jmi.v21i2.2703
|View full text |Cite
|
Sign up to set email alerts
|

Does The Efficient Market Theory In The Weak Form Exist? Evidence From Indonesia

Abstract: In the weak-form market efficiency theory, investors cannot predict the movement of all prices because of randomness. This circumstance happens because of a quick market reaction to new information. Conversely, suppose the market is not efficient in this shape; in that case, the investors can obtain an abnormal return. One of the reasons is the thin market, where many inactive stocks to be traded are available. Based on these issues, this research intends to examine this theory by employing runs testing on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Applying the Efficient Market Hypothesis (EMH) in this prediction study aligns with other findings that have indicated that predictions can be made if the market index has a market efficiency status that matches EMH. Several previous studies (Faisal et al, 2022;Hadianto et al, 2021;Jawadi et al, 2015;Kasidi & Banafa, 2022;Rodoni et al, 2022;Rossi & Gunardi, 2018;Santoso & Ikhsan, 2020) have also supported the idea that the possibility of accurate prediction can be obtained from an efficient market according to EMH. One of the implications of EMH is that if the market has been efficient, then all relevant information has already been reflected in the stock price, thus making price predictions more reliable.…”
Section: Discussionmentioning
confidence: 63%
“…Applying the Efficient Market Hypothesis (EMH) in this prediction study aligns with other findings that have indicated that predictions can be made if the market index has a market efficiency status that matches EMH. Several previous studies (Faisal et al, 2022;Hadianto et al, 2021;Jawadi et al, 2015;Kasidi & Banafa, 2022;Rodoni et al, 2022;Rossi & Gunardi, 2018;Santoso & Ikhsan, 2020) have also supported the idea that the possibility of accurate prediction can be obtained from an efficient market according to EMH. One of the implications of EMH is that if the market has been efficient, then all relevant information has already been reflected in the stock price, thus making price predictions more reliable.…”
Section: Discussionmentioning
confidence: 63%
“…Thirdly, the strong assumption concerns the state of an efficient market, where stock prices reflect all information relevant to the company, including information only available to company insiders. For example, in the Indonesian capital market, the weak assumption is that global economic information such as the FED rate, crude oil prices, and CPO will more easily affect stock prices [19][20][21].…”
Section: Efficient Market Hypothesismentioning
confidence: 99%